Global trends and research gaps in deep brain stimulation for neurodevelopmental disorders: a scientometrics exploration of functional and behavioral outcomes - Acuña-Rodriguez, Mónica; Montoya-Quintero, Kevin Fernando; Visconti-Lopez, Fabriccio J.; Martinez-Royert, Judith Cristina (Frontiers in Human Neuroscience, 2025)
IntroductionDeep brain stimulation has emerged as a potential intervention for improving functional outcomes and behavioral regulation in individuals with neurodevelopmental disorders. However, the extent to which these clinical endpoints have been systematically studied remains unclear.MethodsA comparative scientometrics analysis was conducted to map the research landscape on deep brain stimulation in neurodevelopmental disorders (n = 833 publications) and a focused subset addressing functional performance and aggressiveness (n = 52). We used Bibliometrix in R and Matplotlib in Python to analyze studies published between 1996 and June 2025.ResultsWe found a sustained increase in publication volume since 1996, but only 6.2% of studies explicitly addressed functional or behavioral endpoints. Clinical trials and systematic reviews were underrepresented in both datasets (1.20 and 3.12% in the general analysis; 0 and 7.69% in the subset, respectively). High-income countries dominated scientific production, with minimal contributions from lower-income regions. In the focused subset, Colombia emerged among the top 3 most productive countries. Keyword analyses revealed a thematic concentration on diagnostic categories rather than outcome-based evidence.DiscussionThese findings highlight critical research gaps and suggest a misalignment between current scientific focus and the clinical potential of deep brain stimulation in neurodevelopmental disorders. Future studies should focus on functional improvement and behavioral modulation to bridge this divide and support the development of evidence-based, patient-centered applications of deep brain stimulation in individuals with neurodevelopmental disorders.